PENERAPAN PENDEKATAN TPACK UNTUK MENINGKATKAN KEMAMPUAN PENULISAN HURUF KAPITAL SISWA KELAS III SD NEGERI BLANG BINTANG ACEH BESAR - Aprillia Eka Putri, Putri Rahmi; Putri Rahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted with the aim of seeing the improvement of students' capitalization writing ability in grade III of Blang Bintang Elementary School, Greater Aceh. This study used a classroom action research method consisting of 2 cycles, each cycle includes the planning, implementation, observation, and reflection stages. The subjects in this study were 18 grade III students, consisting of 12 males and 6 females. To observe the activities of teachers and students, an observation sheet was used, while a test sheet was used to measure the results of capitalization writing ability. The results of the study showed a significant increase; teacher activity increased from 88.7% in cycle I to 92.2% in cycle II, while student activity increased from 74.3% to 84.1%. The results of the capitalization writing ability test also increased from 59.7% in cycle I to 83.3% in cycle II. This study shows that the use of the TPACK approach is very effective in improving teacher activity, student activity and capitalization writing ability of grade III students of Blang Bintang Elementary School.